Da-Chai-Hu Decoction Ameliorates High Fat Diet-Induced Nonalcoholic Fatty Liver Disease Through Remodeling the Gut Microbiota and Modulating the Serum Metabolism - Cui, Huantian; Li, Yuting; Wang, Yuming; Jin, Lulu; Yang, Lu; Wang, Li; Liao, Jiabao; Wang, Haoshuo; Peng, Yanfei; Zhang, Zhaiyi; Wang, Hongwu; Liu, Xiangguo (Frontiers in Pharmacology, 2020)
The dysbiosis in gut microbiota could affect host metabolism and contribute to the development of nonalcoholic fatty liver disease (NAFLD). Combining the 16S rRNA sequencing with metabolomics approaches can further explain the mechanisms of Chinese herbal formulas through studying the interactions between gut microbiota and host metabolism. Da-Chai-Hu decoction (DCH) has demonstrated with protective effects on NAFLD. However, the exact mechanisms of DCH on NAFLD remain unclear. In this study, we established a NAFLD rat model using high fat diet (HFD) and treated with DCH. The changes of gut microbiota after DCH treatment were investigated using 16S rRNA sequencing. Besides, serum untargeted metabolomics were performed to study the metabolic regulations of DCH on NAFLD. Results showed that DCH treatment improved the dyslipidemia, insulin resistance (IR) and ameliorated pathological changes in NAFLD model rats. In addition, 16S rRNA sequencing and untargeted metabolomics showed significant dysfunction in gut microbiota community and serum metabolites. DCH treatment restored the dysbiosis of gut microbiota and improved the dysfunction in serum metabolism. Correlation analysis indicated that the regulatory effects of DCH on arachidonic acid (AA) metabolism pathway, glycine, serine and threonine metabolism pathway and glycerophospholipid metabolism pathway were related to the alteration of the Romboutsia, Bacteroides, Lactobacillus, Akkermansia, Turicibacter, Lachnoclostridium and Enterobacteriaceae abundances. In conclusion, our study revealed the ameliorative effects of DCH on NAFLD model rats. The mechanisms of DCH on NAFLD might be related to improve the dysbiosis of gut microbiota and further modulate the AA metabolism, glycerophospholipid metabolism, glycine, serine and threonine metabolism pathways. Our study could open avenues of using multi-omics approaches to elucidate the working mechanism of Chinese formula.